Effects of a physical education program on physical activity, fitness, and health in children: The JuvenTUM project. Issue 3 (29th September 2011) - Siegrist, M.; Lammel, C.; Haller, B.; Christle, J.; Halle, M.
<x xml:space="preserve">Abstract</x> The purpose of the study was to investigate the effects of a school‐based prevention program on physical activity, fitness, and obesity. We performed a prospective study in eight Bavarian primary schools (n = 724 children, 8.4 ± 0.7 years) randomized one to one to either an intervention school (IS, n = 427) or a control school (CS, n = 297). Children in IS attended 10 health‐related lessons at school over a period of 1 year. Parents and teachers attended two and three educational health‐related lessons, respectively, and also received 10 newsletters on health issues. Daily physical activity (≥ 60 min/day), physical fitness (six‐item test battery), and anthropometric data were obtained at baseline and after 1 year. Physical activity and physical fitness increased in IS, but it failed to reach significant intervention effects. Nevertheless, a reduction in waist circumference was observed for all children [mean change 1.7 cm; 95% confidence interval (CI) 1.2–2.3; P < 0.001). This effect was more pronounced in overweight children (> 90th percentile, n = 99, mean change 3.2 cm; 95% CI 1.5–4.8; P < 0.001). This easily administered preventative program involving children, parents, and teachers revealed that a generalized approach increasing physical activity will even be favorable in a subgroup of obese children.